2013
DOI: 10.1007/s10113-013-0497-4
|View full text |Cite
|
Sign up to set email alerts
|

Forest cover changes in North Korea since the 1980s

Abstract: North Korea used to have abundant forest stocks but underwent substantial deforestation and degradation of forest in recent decades. This study examined morphological changes of forest cover in North Korea between the 1980s and 2000s. Land cover data based on Landsat TM imagery were obtained as images from the Republic of Korea's Ministry of Environment. The images were processed and used for the Morphological Spatial Pattern Analysis and network analysis. MSPA classified the forest cover into morphological cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 8 publications
1
30
1
Order By: Relevance
“…Remote sensing from space provides an unprecedented perspective on changing forest cover, allowing continuous maps to be constructed and spatiotemporal patterns of fragmentation to be analysed (Taubert et al , ). Assessments of forest fragmentation have been completed for many countries including Canada, Chile, China, the Democratic Republic of Congo, India, Malaysia, Myanmar, New Zealand, North Korea, Tanzania, the United Kingdom and the USA (Leimgruber et al , ; Watts, ; Ewers et al , ; Kupfer, ; Abdullah & Nakagoshi, ; Echeverria et al , ; Wulder et al , ; Kang & Choi, ; Reddy et al , ; Kukkonen & Käyhkö, ; Shapiro et al , and Li et al , ). Many of these studies highlight that fragmentation is having severe effects on natural ecosystems by increasing isolation, creating edges, and decreasing core areas of habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing from space provides an unprecedented perspective on changing forest cover, allowing continuous maps to be constructed and spatiotemporal patterns of fragmentation to be analysed (Taubert et al , ). Assessments of forest fragmentation have been completed for many countries including Canada, Chile, China, the Democratic Republic of Congo, India, Malaysia, Myanmar, New Zealand, North Korea, Tanzania, the United Kingdom and the USA (Leimgruber et al , ; Watts, ; Ewers et al , ; Kupfer, ; Abdullah & Nakagoshi, ; Echeverria et al , ; Wulder et al , ; Kang & Choi, ; Reddy et al , ; Kukkonen & Käyhkö, ; Shapiro et al , and Li et al , ). Many of these studies highlight that fragmentation is having severe effects on natural ecosystems by increasing isolation, creating edges, and decreasing core areas of habitat.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, North Korea endured so‐called the Arduous March , which refers to the massive famine during the late 1990s and the political slogan to overcome the famine (Hastings, ; Meyer‐Rochow, ). The famine had several causes such as the collapse of the Soviet bloc, ineffective and mismanaged economy, and severe natural disasters and is believed to have led to deforestation during the late 1990s and the 2000s (Kang & Choi, ). We propose that the long‐lasting economic hardship certainly impacted urban land cover changes and land degradation.…”
Section: Resultsmentioning
confidence: 99%
“…According to Yu and Kim [60], forest area was reduced from 91,679 to 73,291 km 2 during 1989-2008, which indicates that 18,388 km 2 of the forest areas were converted to other land-cover categories. Cui et al [3] and Kang and Choi [8] used the same land cover map and showed that 5674 km 2 and 15,820 km 2 were deforested, respectively. These differences in the results can be explained by differences in classification techniques, time scales, spatial resolutions, and types of satellite images used in the respective studies [61].…”
Section: Cropland Expansion and Deforestation In North Koreamentioning
confidence: 99%